Efficacy and mechanism of antitumor activity of an antibody targeting transferrin receptor 1 (TfR1) in mouse models of human multiple myeloma() - Leoh, Lai Sum (J Immunol, 2018)
The transferrin receptor 1 (TfR1) is an attractive target for antibody-mediated cancer therapy. We previously developed a mouse/human chimeric IgG3 antibody (ch128.1) targeting human TfR1, which exhibits direct in vitro cytotoxicity against certain human malignant B cells through TfR1 degradation and iron deprivation. ch128.1 also demonstrates exceptional antitumor activity in two xenograft models of the B-cell malignancy multiple myeloma (MM): SCID-Beige mice bearing disseminated ARH-77 or KMS-11 cells in an early disease setting. Interestingly, this activity is observed even against KMS-11 cells, which show no sensitivity to the direct cytotoxic activity of ch128.1 in vitro. To understand the contributions of the Fc fragment, we generated a ch128.1 mutant with impaired binding to FcγRs and to the complement component C1q, which retains binding to FcRn. We now report that this mutant antibody does not show antitumor activity in these two MM models, indicating a crucial role of the Fc fragment in the antitumor activity of ch128.1, which can be attributed to effector functions (ADCC, ADCP, and/or CDC). Interestingly, in the KMS-11 model, complement depletion does not affect protection, while macrophage depletion does. Consistent with this observation, we found that ch128.1 induces ADCC and ADCP against KMS-11 cells in the presence of murine bone marrow-derived macrophages. Finally, we found that ch128.1 therapy effectively increases survival in a late MM disease setting. Our results suggest that macrophages play a major role in ch128.1-mediated antitumor protection in our models and that ch128.1 can be effective against human B-cell malignancies such as MM.